Increased drug permeability of a stiffened mycobacterial outer membrane in cells lacking MFS transporter Rv1410 and lipoprotein LprG. Issue 5 (18th March 2019) - Hohl, Michael; Remm, Sille; Eskandarian, Haig A.; Dal Molin, Michael; Arnold, Fabian M.; Hürlimann, Lea M.; Krügel, Andri; Fantner, Georg E.; Sander, Peter; Seeger, Markus A.
Summary: The major facilitator superfamily transporter Rv1410 and the lipoprotein LprG (Rv1411) are encoded by a conserved two‐gene operon and contribute to virulence in Mycobacterium tuberculosis . Rv1410 was originally postulated to function as a drug efflux pump, but recent studies suggested that Rv1410 and LprG work in concert to insert triacylglycerides and lipoarabinomannans into the outer membrane. Here, we conducted microscopic analyses of Mycobacterium smegmatis lacking the operon and observed a cell separation defect, while surface rigidity measured by atomic force microscopy was found to be increased. Whereas Rv1410 expressed in Lactococcus lactis did not confer drug resistance, deletion of the operon in Mycobacterium abscessus and M. smegmatis resulted in increased susceptibility toward vancomycin, novobiocin and rifampicin. A homology model of Rv1410 revealed a periplasmic loop as well as a highly conserved aspartate, which were found to be essential for the operon's function. Interestingly, influx of the fluorescent dyes BCECF‐AM and calcein‐AM in de‐energized M. smegmatis cells was faster in the deletion mutant. Our results unambiguously show that elevated drug susceptibility in the deletion mutant is caused by increased drug influx through a defective mycobacterial cell envelope and not by drug efflux mediated by Rv1410. Abstract : The transporter Rv1410 and lipoprotein LprG work in concert to incorporate triacylglycerides into the outer membrane of mycobacteria. Here we show that Mycobacterium smegmatis lacking these two proteins forms a defective outer membrane that is more permeable for drugs and dyes such as BCECF‐AM. In previous studies, Rv1410 was suggested to operate as drug efflux pump. In contrast, our results show that the seeming drug efflux phenotype is due to increased drug influx.